Australians' use of fake tanning lotions: another piece of the puzzle - Afaf Girgis; Flora Tzelepis; Christine L. Paul; Raoul A. Walsh; Patrick McElduff; Jeanie McKenzie (Elsevier, 2003)
Abstract Objective: To assess community attitudes and practices in relation to fake tanning lotions. Methods: 1,509 New South Wales residents aged 15 years and over, selected at random, completed a computer‐assisted telephone survey. Results: Thirty‐three per cent of respondents thought fake tanning lotions were unsafe. In relation to The Cancer Council marketing fake tanning lotions, more than three‐fifths thought The Cancer Council would be promoting tans, although 62% thought it would be a good thing as fake tans are safer than tanning in the sun. Nine per cent of respondents had used fake tanning lotions in the past 12 months. Almost half (48%) of female current users used fake tanning lotions occasionally or only for special occasions during the past summer. In particular settings, the sunscreen and hat‐wearing practices of female users and non‐users of fake tanning lotions differed significantly. Conclusion: There appears to be no consistent data to suggest that fake tanning lotions may be used as a safer alternative to sun tanning. However, there is a responsibility to at least disseminate accurate information on these products.